PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DALAM PERGURUAN TINGGI - Hartini, Kustin (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2015)
Total Quality Management (TQM) is an approach manejemen used to enhance the competitiveness of companies in the long run in a globalized world to be able to compete on a competitive basis. Companies need for radical change to the management system, in order to produce goods or services in accordance with the demands of the times and consistently produce high quality goods or services. Total Quality Management (TQM) or Integrated Quality Management is often linked to other terms such as Quality Improvement Program (QIP) despite having a different principle but interrelated and refer to the same purpose namely improving the quality (quality). Quality factor is very important, because one of the standards of global competition factors other than price(price),and service factors(service).Characteristics of globalization demanding quality requirements not only penetrated the world of business and enterprise but in all aspects and areas of life including education.